Editorial theory and the range of translations for "cedars of Lebanon" in the Septuagint - Miller, Cynthia L. (HTS teologiese studies, 2018)
Although the Hebrew source text term אֶרֶז [cedar] is translated in the majority of cases as κέδρος [cedar] or its adjective κέδρινος in the Septuagint, there are cases where the following translations and strategies are used: (1) κυπάρισσος [cypress] or the related adjective κυπαρίσσινος, (2) ξύλον [wood, tree] and (3) non-translation and deletion of the source text item. This article focuses on these range of translations. Using a complexity theoretical approach in the context of editorial theory (the new science of exploring texts in their manuscript contexts), this article seeks to provide explanations for the various translation choices (other than κέδρος and κέδρινος). It further aims to determine which cultural values of the translators have influenced those choices and how they shape the metaphorical and symbolic meaning of plants as determined by Biblical Plant Hermeneutics, which has placed the taxonomy of flora on a strong ethnological and ethnobotanical basis.